2015
DOI: 10.1186/s12954-015-0056-z
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C and HIV incidence and harm reduction program use in a conflict setting: an observational cohort of injecting drug users in Kabul, Afghanistan

Abstract: BackgroundArmed conflict may increase the risk of HIV and other pathogens among injecting drug users (IDUs); however, there are few prospective studies. This study aimed to measure incidence and potential predictors, including environmental events and needle and syringe distribution and collection program (NSP) use, of hepatitis C virus (HCV) and HIV among IDUs in Kabul, Afghanistan.MethodsConsenting adult IDUs completed interviews quarterly in year 1 and semi-annually in year 2 and HCV and HIV antibody testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(49 citation statements)
references
References 29 publications
0
49
0
Order By: Relevance
“…Two studies did not report needle exchange participation for the number of participants who were HCV seronegative at baseline [44, 45]. With the exception of one study that only enrolled males [45], all other studies enrolled both genders.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies did not report needle exchange participation for the number of participants who were HCV seronegative at baseline [44, 45]. With the exception of one study that only enrolled males [45], all other studies enrolled both genders.…”
Section: Resultsmentioning
confidence: 99%
“…No intervention of interest: no OST or NSP Tait 2013b No outcome of interest. No intervention of interest: no OST or NSP Todd 2015 No intervention of interest (NSP shuts down for some of the follow‐up) Tracy 2014 No intervention of interest: no OST or NSP Tsirogianni 2013 No intervention of interest: no OST or NSP Tsui 2009 No intervention of interest: no OST or NSP Valdez 2011 No outcome of interest. No intervention of interest: no OST or NSP Van Ameijden 1993 No intervention of interest: no OST or NSP Van den Hoek 1990 No outcome of interest Van den Laar 2009 No outcome of interest.…”
Section: Characteristics Of Excluded Studies [Ordered By Study Id]mentioning
confidence: 99%
“…One example is the lower than expected contribution of PWID to total incidence we estimated in Afghanistan and Pakistan – two countries where the epidemic is apparently largely driven by injecting drug use . In Afghanistan, a similar HIV incidence rate of 1.5% ppy was measured among PWID in a cohort study . Under‐reporting of injecting risk behaviour, hidden HIV epidemics among PWID in sites not covered by the IBBSS, and emerging and/or hidden HIV epidemics among other KPs such as MSM in Pakistan, could be potential explanations to the observed lower contribution of PWID to total incidence.…”
Section: Discussionmentioning
confidence: 74%
“…Despite noticeable progress in the collection of HIV prevalence data in MENA, HIV incidence data remain scarce among all populations groups . Among PWID, only three cohort‐type HIV incidence studies have been conducted; in Afghanistan , Pakistan and Iran , and all indicated substantial incidence . Quantifying HIV incidence among PWID in MENA is urgently needed to provide baseline data to track progress towards UNAIDS target of reducing the number of new HIV infections among young people and adults by 75% by 2020 .…”
Section: Introductionmentioning
confidence: 99%